Magnitude and determinants of gender-based violence among female students in Ethiopian higher educational institutions: a systematic review and meta-analysis - Tadesse, Gebresilassie; Tinsae, Techilo; Nakie, Girum; Rtbey, Gidey; Andualem, Fantahun; Kelebie, Mulualem; Kibralew, Getasew; Tadesse Abate, Asnake; Shumet, Shegaye; Melkam, Mamaru; Fentahun, Setegn (Frontiers in Psychiatry, 2024)
Background: Many adolescents are vulnerable to gender-based violence, and it is a major public health issue. Even though the burden of gender-based violence is still high in Ethiopia, there is a lack of summary information to address the problem. Therefore, this study aimed to assess the pooled magnitude and factors associated with gender-based violence among female students in Ethiopian higher educational institutions.Methods: The primary articles were searched using databases like PubMed, Google Scholar, CINAHL, SCOPUS, EMBASE, and African Journal Online. Articles that assessed the magnitude and factors associated with GBV among female students in Ethiopia were included. A Microsoft Excel spreadsheet was used to extract the data, which was then exported to Stata version 14 for further analysis. The statistical heterogeneity was evaluated using the I 2 test. Due to heterogeneity, a random effect meta-analysis model was employed. Publication bias was checked through Egger's weighted regression test and funnel plot.Results: This study included twenty-five primary studies with 13,013 participants. The prevalence of lifetime GBV (n = 7), sexual violence (n = 25), and physical violence (n = 7) was found to be 51. 42% (42.38, 60.46), 46.53% (39.86, 53.21), and 37.93% (24.68, 51.18), respectively. Witnessing their mother's abuse by their father during childhood, a lack of open discussion in the family about reproductive health and related personal issues, alcohol consumption, and tight family control were some of the factors significantly associated with lifetime gender-based violence. Furthermore, those who had drunken friends, a regular boyfriend, multiple sexual partners, and chat chewing were factors significantly associated with lifetime sexual violence.Our findings revealed that half of female students at higher institutions suffered from violence.So it is recommended to provide accessible information about the consequences of GBV and early intervention for students with the above factors.